Aplikasi Semiotika Roland Barthes terhadap Makna Takwa dalam QS. al-Hajj [22]: 37 - falah, zulfikar; rohmah, miftahur (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
AbstractThis article examines how Roland Barthes' semiotics can be used to understand the meaning of piety in QS. Al-Hajj: 37. The author's background involves the application of the definition of piety as it pertains to the role of the physical and spiritual as it has existed in humans. This study aims to ascertain the true meaning of the word